Título Padrão: experiências da religiosidade popular e a via sacra de Monte Santo - Marques da Costa, Neffertite (Em Perspectiva, 2020)
From a provocation in the book Ideias para adiar o fim do mundo, by Ailton Krenak, a brief discussion about the historical narrative, memory and some concepts applied in the study of popular religiosity is presented. The proposal is to be able to tell one more story to postpone the end of the world of popular religious communities that have ceased to exist – Rodeador, Pedra Bonita, Caldeirão and Pau de Colher - or that took a long time to be recognized as they existed for their members – Belo Monte, instead of Canudos. Reflecting on these religious experiences, this article raises the need to study the memory and devotion practices of the Way of the Cross in Monte Santo, as a counterpoint to the reading presented by Euclides da Cunha, in the work Os sertões, and to expand the study of popular religiosity existing in the northeastern hinterland, presenting research sources and suggesting theoretical-methodological references of analysis.